FORECASTING THE DEVELOPMENT OF FLORICULTURE PRODUCTS IN MODERN CONDITIONS OF AGRARIAN ECONOMIC DEVELOPMENT (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
The article examines current trends in the development of the floriculture market, factors influencing the production and sales volumes of flowers, as well as methods for forecasting the development of the floriculture sector under conditions of market transformation. The study investigates the characteristics of demand for floriculture products, seasonal market fluctuations, and the impact of innovative technologies and government support on the development of the industry. Based on economic and statistical analysis, directions for improving the efficiency of floriculture production are proposed, and a forecast for the development of the industry in the near future is presented. Special attention is paid to the prospects for the development of the floriculture market in Uzbekistan.